Corporate Governance from an Islamic Moral Economy Perspective: The Dimensions and Analysis - Muhammad Rizky Prima Sakti; Mohammad Ali Tareq; Hajime Kamiyama (Signifikan: Jurnal Ilmu Ekonomi, 2021)
Corporate governance from Islamic perspective is derived from Islamic worldview, whereby the God is at the apex and human beings are below Him. However, there is no unified definition of corporate governance under shari’ah point of view. To bridge the applicability of Islamic corporate governance model with Islamic moral economy framework, some key questions to be addressed are as follows. (i) do Islamic corporate governance models consistent with the aspiration of Islamic moral economy? (ii) what are the important dimensions of Islamic corporate governance? (iii)  what is the concept of Islamic corporate governance inspired by the ideals of Islamic moral economy? To accomplish the objectives, this paper follows critical review analysis as a methodology, through which it aims to highlight how each Islamic corporate governance model models are being constructed and to compare those models with Islamic moral economy perspective. The paper proposes the suitable model of Islamic corporate governance under the Islamic moral economy perspective.JEL Classification: G34, O16How to Cite:Sakti, M. R. P., Tareq, M. A., & Kamiyama, H. (2021). Corporate Governance from an Islamic Moral Economy Perspective: The Dimensions and Analysis. Signifikan: Jurnal Ilmu Ekonomi, 10(2), 359-378. https://doi.org/10.15408/sjie.v10i2.21511.